A bottom-up approach to evaluate the harmonics and power of home appliances in residential areas. (1st February 2020) - Sun, Yuanyuan; Xie, Xiangmin; Wang, Qingyan; Zhang, Linghan; Li, Yahui; Jin, Zongshuai
Graphical abstract: Highlights: Harmonic couplings of home appliances between supply voltages and currents are strong. Harmonics of home appliance are affected by supply voltage fluctuation and distortion. Various behavioral factors are considered to improve the appliance random usage model. Bottom-up approach can consider the appliance diversity and upgrading replacement. Abstract: With expansion of the urban population, the power consumed by Chinese residential load is increasing rapidly. At the same time, power-electronic devices are widely adopted in home appliances, injecting a great amount of harmonics into the power system, which makes the harmonic problem in residential areas more serious than ever before. In this paper, a bottom-up approach is proposed to evaluate the harmonics of residential energy use. Firstly, a harmonic coupled model is proposed to calculate the harmonics generated by individual nonlinear home appliance. The model directly exhibits the couplings between different order harmonic voltages and currents. Secondly, based on the Markov chain Monte Carlo method, a random usage model is established to determine the usage pattern of home appliances. Various behavioral factors that affect the domestic use of energy in China are considered, and corresponding correction factors are proposed to improve the model accuracy. Thirdly, based on the proposed electrical and random usage models, a bottom-up approach is used to evaluate the harmonics and power of large-scale residential loads. Simulation results are compared with field measurements to verify the accuracy and validity of the proposed method. Furthermore, the proposed methodologies are applied to predict the harmonic generation and power consumption of some rapidly developing harmonic sources such as electric vehicles.